Hairy polyp can be lethal even when small in size. Issue 3 (18th June 2013) - Koike, Yuhki; Uchida, Keiichi; Inoue, Mikihiro; Ohtsu, Kazuya; Tanaka, Takaaki; Otake, Kohei; Tanaka, Koji; Kusunoki, Masato
Abstract A case of sudden cardiopulmonary arrest in a 3‐month‐old girl is presented. The patient had barely recovered from hypoxic encephalopathy when she presented with repeated respiratory distress. Computed tomography and endoscopic analysis revealed a shiny polyp in the lateral wall of the nasopharynx, and this polyp was suspected to be the main cause of respiratory distress. After referral to our hospital, surgical removal was performed, and the histopathological diagnosis was hairy polyp. Hairy polyp is a rare congenital benign tumor that sometimes induces respiratory distress. This polyp can potentially induce a life‐threatening event. In a systematic review of 40 reported cases, polyps of ≤3.0 cm in diameter have a higher risk of respiratory distress than do those >3.0 cm in diameter (P = 0.01). Small hairy polyps may be lethal because of delayed diagnosis. To locate small hairy polyps, physicians should not hesitate to perform further examination because there is the possibility of oversight with only physical examination.